PENGARUH JUMLAH PELARUT PADA PROSES EKSTRAKSI MINYAK KAYU CENGKEH MENGGUNAKAN MICROWAVE - Adhiksana, Arief; Kusyanto, . (Universitas Nahdlatul Ulama Sidoarjo, 2015)
Clove oil is usually produced from the leaves and flowers, while the twigs cloves actually have potential to be exploited. One of the latest methods that can be used is the microwave assisted extraction. The advantages of microwaves is its ability to deliver energy directly to all material, so it can save time compared to conventional extraction methods. This research aims to study the effect of solvents on the extraction using microwaves. The solvent is water because the polar so very good at absorbing microwave. The variables studied were the weight (75-150 grams) and volume of solvent (400-500 ml) , while the microwave power of 264 W. The choice of wood clove oil yield was obtained of 3.89 % on the amount of solvent to 500 ml with weight is 150 grams.